Analisa Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan Surat Kabar Harian Barito Post - Muhammad Ihsan; Sulastini Sulastini; Saladin Ghalib (Universitas Lambung Mangkurat, 2014)
Employee contribution become important if done effectively and right in implemented. Not only in amount of business but also direction of business. Attitudes, effort or intention to work and several organizations supports means a lot in the success of employee performance.The purpose of this research is to investigate the effects of leadership style and corporate culture toward increase employee performance. Using these variables results , for instance Peter Lok (2004), Rini (2010), Julitriarsa, Djati (2012), Rani Mariam (2009).The study was conducted at Daily Newspaper Barito Post , the sample size is about 113 employee, using the Structural Equation Modelling (SEM). The results show the effect of leadership style toward increase employee performance is positive significant; The effect of corporate culture toward increase employee performance is positive significant; The effect of corporate culture style toward leadership style is positiveThe empiric finding, indicated that to increase employees performance at Daily Newspaper Barito Post need to pay attention to factors that influencing employees performance such as leadership style and organizational culture. Because by given the referable the relation, influence to design strategy utilize improvement of employees performance.Keywords: leadership style, corporate culture, and employee Performance